Andai-Andai Folk Tale: A Tool to Promote Eco-Social Values among Children in Kedurang Community - Junaidi, Febi; Permatasari, Sinta Dewi; ., Srimaryani; Silviana, Zindi Jenika; Metboki, Maria Yolanda; Hidayat, Amar Noor; Dompeipen, Amanda Christin; Rumohoira, Delta Richelly (Journal of Ecohumanism, 2024)
Folk tales serve as a conduit for imparting knowledge concerning the natural environment and social mores to children. The ’Andai-Andai’ folk tales within the context of Kedurang assumes a pivotal role in instilling ecological and societal principles in the succeeding generation. This study seeks to investigate the prevalence of the ’Andai-Andai’ folk tales and its efficacy in instilling social acumen among students in Kedurang, Bengkulu. The research corpus comprises ’Andai-Andai’ folk tales titled "The Clever Orphan," "The Promise of the Buffalo," and "The Buffalo and Beteri." The findings reveal a scarcity in the transmission of ’Andai-Andai’ folk tales to the younger demographic. The ’Andai-Andai’ folk tales epitomize commendable ecological and social values instilled in children from an early age. The monarch depicted in the ’Andai-Andai’ folk tales emerges as a figure characterized by elevated social empathy, fostering community welfare and exemplifying effective leadership. Similarly, the character of Beteri embodies compassion towards others, serving as an exemplar of virtue and beauty. Furthermore, the orphan’s portrayal depicts filial devotion towards his grandmother alongside devout religious observance. Additionally, the ’Andai-Andai’ folk tales encapsulate the natural milieu of Kedurang, as evidenced by references to elements such as rice fields, buffalo, forests, villages, and rivers. The study findings underscore the significance of preserving ’Andai-Andai’ folk tales and highlight community ardor towards this endeavor, recognizing these stories as repositories of environmental knowledge and moral values indispensable for posterity.